2019
DOI: 10.56093/ijas.v89i6.90758
|View full text |Cite
|
Sign up to set email alerts
|

Water dynamics, productivity and heat use efficiency responses in wheat (Triticum aestivum) to land configuration techniques and irrigation schedules

Abstract: The present study was conducted during 2012–13 and 2013–14 to investigate the effect of different land configurations and irrigation schedules on soil water depletion, ground water contribution (GWC), productivity and heat use efficiency of wheat (Triticum aestivum L. emend. Flori & Paol). Results of the two years study exhibited highest grain yield by 24.7% and 17.4%, water use efficiency (WUE) by 38.8% and 35.7%, respectively, under furrow irrigated raised beds (FIRBS) over conventional tillage (CT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This can be affordable for smallholder farmers with limited labour who often face water and labour shortages. This result also agrees with the summary provided by Gupta et al (2017), Hossain et al (2014), Rajanna et al (2016) and Mekonnen et al (2012), who reported that the NSPP increases with an increase in irrigation water amount.…”
Section: Response Of Haricot Bean Crop Yield Attributes To Sisupporting
confidence: 93%
“…This can be affordable for smallholder farmers with limited labour who often face water and labour shortages. This result also agrees with the summary provided by Gupta et al (2017), Hossain et al (2014), Rajanna et al (2016) and Mekonnen et al (2012), who reported that the NSPP increases with an increase in irrigation water amount.…”
Section: Response Of Haricot Bean Crop Yield Attributes To Sisupporting
confidence: 93%
“…Concurrently, application of surplus supplemental irrigation (SSI) & narrow row spacing noted highest water use efficiency (WUE), while deficit supplemental irrigation (DSI) at reproductive stage with broader row spacing noted with less WUE [ 46 ]. Rajanna and Dhindwal [ 32 ] reported that the raised bed planting of wheat saved 15–35% irrigation water through higher irrigation water productivity.…”
Section: Discussionmentioning
confidence: 99%
“…After irrigation, the depth of water in each plot was measured at 10 selected spots using a measuring scale. Crop water productivity (CWP) and irrigation water productivity (IWP) were computed using the expressions 8 and 9, as provided by Rajanna et al [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that our study focused on soil bacterial communities, soil fungi play an important role in SOC cycling 51 . Furthermore, soil fungi and their oxidative enzymes play a key role in the degradation of organic matter compounds with condensed aromatic ring structures, such as cellulose and lignin 52 . As a result, fungi are an excellent target for future research into the effects of rice residue on soil microbial communities.…”
Section: Discussionmentioning
confidence: 99%